PS01.030: ROBOTIC LAPAROSCOPIC HELLER-DOR FOR ACHALASIA: SINGLE INSTITUTION'S EXPERIENCE ON 89 FIRST PATIENTS. (14th September 2018) - Rasanen, Jari
Abstract: Background: Robotics allows precise dissection during the Heller-Dor. We wanted clarify whether this has produced good results in achalasia treatment of our patients in our institution. Methods: We reviewed eighty-nine patients who were treated with robot-assisted laparoscopic Heller-Dor between October 2010 and January 2018 at Helsinki University Hospital. They all underwent laparoscopic myotomy for achalasia extending 8 cm onto esophagus and 3 cm onto proximal stomach with partial Dor fundoplication by two surgeons. Diagnosis of achalasia was confirmed by radiography, endoscopy, and manometry. Success of the myotomy was verified by intraoperative EGD, postoperative contrast radiography, and subjective postoperative symptom recording. Results: There were 44 men and 45 women, with a mean age 43 + /- 15 years. Thirty-three percent of patients reported weight loss and 95% of patients experienced dysphagia at least once every week preoperatively. Mean operative time was 124 + /- 34 minutes. There were no conversions. Intraoperatively there were 6 patients with minor tears in mucosa of esophagus and 1 patient with minor tear in the mucosa of stomach. They were all recognized and repaired intraoperatively without any significant consequences to the patients (no deaths or ICU admissions). Median hospitalization was 4 days (2 - 17). Postoperatively 93% of patients reported significant improvement in dysphagia. All 6 patients with intra-operative mucosal tear experienced good or excellent symptom relief. Three of patients experienced significant pain in their esophagus even after surgery. All patients but 3 rated their overall symptom control either excellent or good after median follow-up of 31 months. Conclusion: Robotic-assisted laparoscopic Heller-Dor is feasible with good median term results although some patients may experience intraoperative mucosal tears during the learning curve Disclosure: All authors have declared no conflicts of interest.